Kinesiotherapeutic Possibilities and Molecular Parameters in Multiple Sclerosis - Katarzyna Wiszniewska; Małgorzata Wilk; Małgorzata Wiszniewska; Joanna Poszwa; Oliwia Szymanowicz; Wojciech Kozubski; Jolanta Dorszewska (Sclerosis, 2025)
Multiple sclerosis (MS) is a chronic and incurable neurological disease of the central nervous system. Three main forms of the disease have been distinguished: relapsing–remitting form (RRMS), secondary progressive form (SPMS), and primary progressive form (PPMS). Currently, in patients with MS, in addition to pharmacotherapy, neurorehabilitation is indicated to improve the motor function of the body and action in the most physiological movement patterns possible. In this therapy, work on lost or incorrect functions is used to provide the patient with self-sufficiency in everyday life. Kinesiotherapy is used as part of neurorehabilitation. This therapy for MS includes coordination exercises aimed at facilitating movement, strengthening exercises and resistance training, balance exercises, improving stability during everyday activities stretching and relaxation exercises, improving tissue elasticity, reducing tension, and breathing exercises. In this article, we present various possibilities for using kinesiotherapy in patients with MS at various stages of disease development. Moreover, we would like to draw attention to the benefits of physical activity leading to a significant improvement in the quality of life in MS patients. We believe that a regular exercise program should be part of the neurorehabilitation program in these patients in the future.